Central Identities Secondary Identities: Difference and Management, In Elia Abu Madi'sPoem: "The Little Stone" - Bouladjine, Kadour; Rachdi, Hassan (Milev Journal of Research and Studies, 2023)
This study: identity representations, their diversity and ways to be managed, is meant to immask one of the most complicated modern issues about the conflict and coexistence of identities and their representations and success and failure in management because it is impossible for a society to exist without it as it bears noble humanities and a long history full of mobile contradictions and conflicts though the original principles which are considered to be the fundamental constants of identity preservation. This study tackles many perspectives: identity definition and it representations, mobility or stability, diversity or closure, success or failure in its administration.